PATTERN OF FACIAL GUNSHOT AND BLAST INJURIES AMONGST LAW ENFORCING FORCES: Facial Gunshot and Blast Injuries - Khan, Muhammad Nazir; Shah, Syed Amjad; Malik, Zakaullah; Ahmed, Ashfaq; Asim, Muhammad Adil (Pakistan Armed Forces Medical Journal, 2016)
Objective: To assesses the pattern of maxillofacial gunshot and blast injuries amongst law enforcing forces personnel. Study Design: Descriptive Study. Place and Duration of Study: Combined Military Hospital Lahore from Jan 2010 to Dec 2010. Materials and Methods: This prospective study evaluated 52 patients from Jan 2010 to Dec 2010 at Combined Military Hospital (CMH), Kohat Pakistan. All patients in this study were males as fighting corps of law enforcing forces comprises only male soldiers and officers. Patients aged from 18 to 50 years with mean age 29.12 years ± 8.56 years. They were assessed for presence of gunshot and ballistic injuries by clinical examination and evaluation of necessary radiographic investigations. Results: Nineteen patients out of total 52 patients had no other injury which accounts for about 36.9%. In maxillofacial area upper third of face was most frequent site to receive gunshot and ballistic injuries as 10 patients received injuries to upper face which measures about 19.2%. Along with maxillofacial area upper limbs were most common site affected as 14 patients received injuries to upper limbs which is 26.9% of all patients. Conclusion: Gunshot wounds present a great challenge to oral and maxillofacial surgeons and a multidimensional team approach is required to rehabilitate the victims of gunshot injuries.